2004
DOI: 10.1001/archpsyc.61.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow in the Amygdala and Medial PrefrontalCortex During Traumatic Imagery in Male and Female Vietnam Veterans With PTSD

Abstract: These results suggest a reciprocal relationship between medial prefrontal cortex and amygdala function in PTSD and opposing associations between activity in these regions and symptom severity consistent with current functional neuroanatomic models of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
488
3
12

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 714 publications
(559 citation statements)
references
References 44 publications
40
488
3
12
Order By: Relevance
“…The impaired extinction retention in the PTSD subjects in the present study is consistent with studies reporting deficient activation of this brain region in PTSD (Shin et al, 2004;Bremner et al, 2005;Liberzon et al, 2003;Phan et al, 2006;Britton et al, 2005;Shin et al, 2001). Moreover, a recent twin study reported acquired gray matter reduction in an area of vmPFC (rostral anterior cingulate cortex) in PTSD (Kasai et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The impaired extinction retention in the PTSD subjects in the present study is consistent with studies reporting deficient activation of this brain region in PTSD (Shin et al, 2004;Bremner et al, 2005;Liberzon et al, 2003;Phan et al, 2006;Britton et al, 2005;Shin et al, 2001). Moreover, a recent twin study reported acquired gray matter reduction in an area of vmPFC (rostral anterior cingulate cortex) in PTSD (Kasai et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…All correlations are reported for po0.05, two-tailed. ANOVAs examining amygdala volume and function were conducted both including and excluding the subjects meeting PTSD, as PTSD has been associated with both increased (Protopopescu et al, 2005;Shin et al, 2004), and decreased amygdala activity (Britton et al, 2005); amygdala volume in PTSD has been shown not to be different from controls (Bremner, 2002;Wignall et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Hyporesponsive PFC, as well as reduced connectivity to the amygdala (Jin et al, 2013;Shin et al, 2004a) may indicate insufficient inhibitory control over exaggerated fear responses. Lastly, abnormal hippocampal function (Corcoran and Maren, 2001) and reduced connectivity to the amygdala (Dolcos et al, 2004;McGaugh, 2004) may underlie impairments in contextual memory processing and the ability to inhibit intrusive memories (Shin et al, 2004a), although findings have been mixed (Hughes and Shin, 2011). A recent resting-state fMRI study showed increased activity in amygdala and reduced spontaneous neural activity in the dorso-lateral PFC (DLPFC) (Yan et al, 2013).…”
Section: Clinicalmentioning
confidence: 99%